2020
DOI: 10.1177/0272431620950478
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Media Multitasking Behavior and Executive Function in Adolescence: A Replication Study

Abstract: The proliferation of digital gadgets and increased media consumption among adolescents has raised interest and concern regarding possible effects on cognitive functioning. Research investigating this relationship has yielded mixed results. This study aims to replicate the research conducted by Baumgartner et al. concerning the relationship between adolescent media multitasking and executive functioning on a sample of 296 Romanian early adolescents. The same methodology as the original study was followed and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
(145 reference statements)
3
11
0
2
Order By: Relevance
“…On the other hand, there is an emerging pattern of evidence showing no differences between HMMs and LMMs on shifting, or even no association between media multitasking score and shifting (Cardoso-Leite et al, 2016;Gorman & Green, 2016;Minear et al, 2013;Seddon et al, 2018). For example, Rogobete et al (2020) considered media multitasking with media activities and non-media activities, and found that the relationship between media multitasking and shifting was not significant; the researchers further doubted that there was a non-linear relationship between media multitasking and executive function. This finding provides strong evidence to query whether there are significant between-group differences between HMMs and LMMs on shifting aspect with methodological triangulation; and replication studies are therefore needed in the future.…”
Section: Hmms Versus Lmms: the 3-level Differences And The Neurocognitive Causesmentioning
confidence: 99%
“…On the other hand, there is an emerging pattern of evidence showing no differences between HMMs and LMMs on shifting, or even no association between media multitasking score and shifting (Cardoso-Leite et al, 2016;Gorman & Green, 2016;Minear et al, 2013;Seddon et al, 2018). For example, Rogobete et al (2020) considered media multitasking with media activities and non-media activities, and found that the relationship between media multitasking and shifting was not significant; the researchers further doubted that there was a non-linear relationship between media multitasking and executive function. This finding provides strong evidence to query whether there are significant between-group differences between HMMs and LMMs on shifting aspect with methodological triangulation; and replication studies are therefore needed in the future.…”
Section: Hmms Versus Lmms: the 3-level Differences And The Neurocognitive Causesmentioning
confidence: 99%
“…For associations with working memory only three studies have used self-report measures (Baumgartner et al, 2014;Magen, 2017;Rogobete et al, 2020). In all three, the WM subscale of the BRIEF was used.…”
Section: Self-report Findingsmentioning
confidence: 99%
“…As with assessments for self-reported WM, only three studies (Baumgartner et al, 2014;Magen, 2017;Rogobete et al, 2020) have used self-report measures to consider associations between media multitasking and task management. In all three cases the shifting subscale of the BRIEF was used.…”
Section: Self-report Findingsmentioning
confidence: 99%
“…Other studies did not always replicate these results Elbe, Sörman, Mellqvist, Brändström, & Ljungberg, 2019;Minear et al, 2013;Seddon, Law, Adams, & Simmons, 2018) or suggested that the relationships between levels of media multitasking and cognitive performance may be non-linear (Cardoso-Leite et al, 2016;Shin, Linke, & Kemps, 2020). The results seem clearer when using surveys and self-reports rather than computerized tests (Magen, 2017): media multitasking has been associated with deficits in self-reported everyday executive and attentional functions (Baumgartner, Weeda, Heijden, & Huizinga, 2014;Magen, 2017;Ralph et al, 2014;Rogobete, Ionescu, & Miclea, 2020) and could be particularly detrimental at younger ages where executive functions develop intensely (Baumgartner, van der Schuur, Lemmens, & te Poel, 2018; see also Srisinghasongkram, Trairatvorakul, Maes, & Chonchaiya, 2020).…”
Section: Media-multitaskingmentioning
confidence: 99%